The Present Status of Hydrography in Papua New Guinea - Done, P. (The International Hydrographic Review, 2015)
The importance to Papua New Guinea of water-borne transport is emphasized and the current status of hydrography in its waters is assessed. Current requirements are reviewed and recommendations as to future policy made.